Risk factors for bacteremia and central line–associated blood stream infections in children with acute myelogenous leukemia: A single‐institution report. Issue 3 (12th September 2016) - Rogers, Ashley E. J.; Eisenman, Kristen M.; Dolan, Susan A.; Belderson, Kristin M.; Zauche, Jocelyn R.; Tong, Suhong; Gralla, Jane; Hilden, Joanne M.; Wang, Michael; Maloney, Kelly W.; Dominguez, Samuel R.
Abstract: Background: Central line–associated blood stream infections (CLABSIs) are a source of high morbidity and mortality in children with acute myelogenous leukemia (AML). Procedure: To understand the epidemiology and risk factors associated with the development of CLABSI in children with AML. Methods: We retrospectively reviewed all patients with AML over a 5‐year period between 2007 and 2011 at the Children's Hospital Colorado. Cases and controls were classified on the basis of the presence of a CLABSI as defined by the National Healthcare Safety Network. Results: Of 40 patients in the study, 25 (62.5%) developed at least one CLABSI during therapy. The majority of CLABSIs were due to oral or gastrointestinal organisms (83.0%). Skin organisms accounted for 8.5%. In a multivariable analysis, the strongest risk factors associated with CLABSI were diarrhea (odds ratio [OR] 6.7, 95% confidence interval [CI] 1.6–28.7), receipt of blood products in the preceding 4–7 days (OR 10.0, 95%CI 3.2–31.0), not receiving antibiotics (OR 8.3, 95%CI 2.8–25.0), and chemotherapy cycle (OR 3.5, 95%CI 1.4–8.9). CLABSIs led to increased morbidity, with 13 cases (32.5%) versus two controls (1.9%) requiring transfer to the pediatric intensive care unit ( P < 0.001). Three (7.5%) of 40 CLABSI events resulted in or contributed to death. Conclusions: Intensified line care efforts cannot eliminate all CLABSIs in the patients with AML. Exploring the role of mucosal barrier breakdown and/or the use of antibiotic prophylaxis may be effective strategies for further prevention of CLABSIs, supporting ongoing trials in this patient population.